[Rezension von: Grund, Peter J., The sociopragmatics of stance] - Landert, Daniela (English language and linguistics, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1360674323000023/resource/name/firstPage-S1360674323000023a.jpg